Comparison of Physicochemical Characteristics of Margarine and Butter in Iranian Market During Storage - Narges Esmaeilifard; Manochehr Bahmaei; Parvin Eshratabadi (Islamic Azad University, 2016)
Margarine contains a higher level of unsaturated and trans-fatty acids (TFA) than butter. The aim of this study was to investigate the physicochemical properties of these products in Iranian market during storage. Physicochemical analyses included fatty acid composition, peroxide and Anisidine values, slip melting point (SMP), color, chlorophyll content, solid fat content (SFC) and texture analysis. Margarine, compared to the butter, contained a higher degree of unsaturation, TFA, SMP, peroxide and Anisidine than butter. Predominant TFA in butter and margarine were vaccenic (about 2.83-3.41%) and elaidic acids (about 7.55-9.26%), respectively. Peroxide and Anisidine values of margarine increased significantly during storage. a* value and SMP of all samples increased significantly during storage. The SMP of margarine-2 was more than that of other samples. Chlorophyll content of butter was significantly more than margarine. Also, the content of chlorophyll of all samples was constant during storage. L* and b* values of all samples decreased significantly during storage. SFC of butter was significantly (p<0.05) more than margarine at 5 to 10°C, but at temperatures ranging 20 to 35.5°C, SFC of margarine-2 was more than butter and margarine-1. At 5°C, a yield value of butter was significantly more than margarine-2, but at 20 and 30°C, a yield value of margarine-2 was more than butter and margarine-1. As a result, the comparison between butter and margarine showed that butter is superior in terms of qualitative factors. However, if the hydrogenation process in the manufacturing of margarine is removed and replaced by other safe methods it can lead to products with high nutritional value.